Optimización de procesos en la unidad de control de bienes de la Universidad Técnica de Cotopaxi - Caiza Mejía, Cristian Andrés (2022)
The present research project focuses basically on optimization processes of property unit control at Technical University of Cotopaxi, the main problem was related to physical verification process of the institution's fixed assets, which does not have a system for identification and registration of goods, as well as goods classification and distribution for use and current consumption to optimize physical space of warehouses units. The project objective is to provide solutions to the problems that arise in the unit in order to be able to develop the activities effectively and eliminate all types of errors that may occur. To develop this project, descriptive research was used, which helped to determine key points of the processes; the methods used were deductive, inductive and synthetic analysis which were put into practice for the development of objectives; techniques that were used to carry out the information gathering were; observation, survey, interview, questionnaire, flow diagrams and cause - effect. Thanks to what has already been exposed, it was possible to design proposals for main unit problems, obtaining as a result time and efforts reduction at physical verification process of fixed assets and warehouse organization with goods used for current consumption, verifying operational and economic viability of proposals in order to guarantee processes optimization at goods control unit through its implementation.